Race, Racism, And Science - Social Impact And Interaction - Cumo, Christopher (Teaching History: A Journal of Methods, 2007)
In a lucid account, John P. Jackson and Na dine M. Weidman trace the origin, development, and decline of the concepts of race and racism within the context of the discourse among scientists about these concepts. The authors define science broadly to include the natural and social sciences. The concepts of race and racism, rooted in medieval Spain, predate the rise of experimental science.